2014
DOI: 10.1155/2014/627028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Oxygen on Maternal and Neonatal Oxygenation in Elective Cesarean Section under Spinal Anesthesia: A Randomized Controlled Trial

Abstract: The use of supplemental oxygen in uncomplicated cesarean deliveries under spinal anesthesia has been thoroughly investigated during recent decades. The aim of this study was to determine the benefits for both mother and infant of administering supplemental, low-dose oxygen via a nasal cannula versus having no supplement (i.e., room air only). Healthy parturients at term undergoing elective cesarean section under spinal anesthesia were randomly allocated into two groups: an oxygen group (n = 170), who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…Similar to other studies, there was no evidence of decompensation in short term clinical outcome (10,20). All episodes of oxygen desaturation were attended to promptly and managed appropriately to minimize the duration of desaturation and/or hypotension.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to other studies, there was no evidence of decompensation in short term clinical outcome (10,20). All episodes of oxygen desaturation were attended to promptly and managed appropriately to minimize the duration of desaturation and/or hypotension.…”
Section: Discussionsupporting
confidence: 82%
“…Our incidence of 1.2% is low compared to 3.7% and 7.4% in two recent studies (10,17). In our study, all three episodes of desaturation were associated with hypotension, similar to the study by Siriussawakul et al who reported that nine out of twelve events were attributed to intraoperative hypotension and the other three due to sedatives administration (10). In contrast, a much higher incidence of desaturation following regional anaesthesia (75-87%) was seen in studies involving non-obstetric surgeries (18,19).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…According to this, women undergoing CS under regional anaesthesia should receive supplemental oxygen to provide extra stores of oxygen to prevent intraoperative or post‐natal foetal hypoxia. Previous studies have shown that administration of 35–40% maternal oxygen did not produce sufficient increase in foetal PO 2 and rather exposed women to unnecessary oxygen therapy . On the contrary, oxygen inhalation of 60–100% during elective CS was known to increase arterial oxygen and oxygen free radicals both in mother and the foetus .…”
mentioning
confidence: 96%